Bioactive compounds and antioxidant attribute of carambola (Averrhoa carambola L.) fruit as affected by cultivars and ripening stages - Mohd Zainudin, Mohd Asraf (2013)
Study on bioactive compounds and antioxidant activity was conducted on three different carambola cultivars (B2, B17 and B10) planted in Malaysia and the best cultivars in terms of antioxidant potential was selected and evaluatedat different ripening stages. Carambola fruits were analyzed for ascorbic acid(AA), total phenolic compound (TPC), total flavonoid content (TFC), total carotenoid content (TCC), beta-carotene (β-carotene), tocopherols (alpha,α;beta,β;gamma,γ and delta,δ) and sugars (glucose, fructose and sucrose). Free radical scavenging activity using 2,2-diphenyl-2-picrylhydrazyl assay (DPPH) and β–carotene-linoleic acid model (BCLAM) assays were performed to evaluate their antioxidant activities. Results of the study showed thatthere is no significant difference in AA content between cv. B2 and cv. B17. Among the cultivars, cv. B17 was found to contain significantly (P<0.05) higher TPC, sugars, β–carotene and β-tocopherol levels while cv. B10 only had significantly (P<0.05) higher content of γ– and δ-tocopherols. However, cv. B10 and cv. B17 did not show any significant difference in TCC, TFC, β-carotene and α- tocopherol content. The study showed that each cultivar had their own advantages in terms of bioactive compounds that could contribute to antioxidant activity. As expected, cv. B10 and cv. B17 exhibited significantly (P<0.05) higher antioxidant activity than that of cv. B2 for both DPPH and BCLAM assays. However, BCLAM result showed that cv. B17 had the highest antioxidant activity among the cultivars.Pearson’s correlation and Partial Least Square (PLS) were used to identify the linkbetween antioxidant activity and bioactive compounds.Carambola cv. B17 had been selected forquantifying the bioactive compounds and antioxidant activity changes at different ripening stages. Carambola cv. B17 was tagged at fruit set stage and harvested at week 9,10,11,12 and 13. Ascorbic acid, TCC and sugar composition were significantly (P<0.05) increased while TPC, TFC and β-carotene exerted the reverse trend during ripening. Tocopherols homologue changes were varied where α– and β–tocopherols levels wereincreased until week 12 before decreased in week 13. On the contrary, γ– and δ–tocopherolslevels were significantly (P<0.05) decreased during ripening. Fruitsharvested at a later ripening stage allow for the synthesis and accumulation of bioactive compounds,thus explained the increasing trend. On the other hand, decreased trend in the bioactive compounds are probably due to their functions as precursor compounds. Antioxidant activities of the samples were significantly (P<0.05) decreased as measured by DPPH and BCLAM assays.Multivariate analysis revealed clear separations between the ripening stagescaused bytransitional changes in bioactive compounds and antioxidant activity during fruit ripening. In conclusion, bioactives compound and antioxidant activity were cultivar- and ripening stage-dependent. Carambola fruit cv. B17 was found to be the best cultivar in terms of antioxidant potential and should be harvestedat week 9 to get its full benefit of antioxidant property.